The Series of Leaflets as Media for Education, Promotion and Monitoring of Exclusive ASI - Bety Agustina Rahayu; Debby Yulianthi Maria; Dwi Hariyanti (Universitas 'Aisyiyah Yogyakarta, 2020)
Mother's knowledge about the importance of exclusive breastfeeding is a problem that determines the success of exclusive breastfeeding. Information support is needed to increase the mother's knowledge. This research create an acceptable media for increasing mother's knowledge of exclusive breastfeeding. This research uses the action research method. There are 5 stages including diagnosis, making an action plan, acting, evaluating and learning. The informants of this research are the baby mothers, posyandu cadres and the ASI counselling team at the Pleret health centre. Data collection instruments and techniques using questionnaires and interviews. Credibility test with technical triangulation, which was analyzed using theories from Milles and Huberman. The creation of a series of leaflet media about exclusive breastfeeding guidelines consisting of six series. Leaflets are made attractive in terms of design. This series of leaflet media can be used as an educational and promotional media about exclusive breastfeeding.